2016
DOI: 10.1038/srep33198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allergic diseases and age on the composition of serum IgG glycome in children

Abstract: It is speculated that immunoglobulin G (IgG) plays a regulatory role in allergic reactions. The glycans on the Fc region are known to affect IgG effector functions, thereby possibly having a role in IgG modulation of allergic response. This is the first study investigating patients’ IgG glycosylation profile in allergic diseases. Subclass specific IgG glycosylation profile was analyzed in two cohorts of allergen sensitized and non-sensitized 3- to 11-year-old children (conducted at University of Aberdeen, UK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Immunoglobulin G was isolated from 500 µl of mouse serum on 96-well Protein G monolithic plates (BIA Separations) as described previously (Pezer et al, 2016). Briefly, serum samples were diluted in 1.4 ml of 1× PBS (prepared in-house from analysis-grade reagents), filtered through AcroPrep Advance 0.45 µm hydrophilic polypropylene (GHP) filter plates (Pall Corporation), bound to the protein G monolith in 1 × PBS, eluted in 0.1 M formic acid (Merck), and neutralized with 1 M ammonium bicarbonate (Merck).…”
Section: Analysis Of Igg Fc-linked N-glycosylation With Liquid Chromamentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoglobulin G was isolated from 500 µl of mouse serum on 96-well Protein G monolithic plates (BIA Separations) as described previously (Pezer et al, 2016). Briefly, serum samples were diluted in 1.4 ml of 1× PBS (prepared in-house from analysis-grade reagents), filtered through AcroPrep Advance 0.45 µm hydrophilic polypropylene (GHP) filter plates (Pall Corporation), bound to the protein G monolith in 1 × PBS, eluted in 0.1 M formic acid (Merck), and neutralized with 1 M ammonium bicarbonate (Merck).…”
Section: Analysis Of Igg Fc-linked N-glycosylation With Liquid Chromamentioning
confidence: 99%
“…Isolated IgG was dried in the vacuum concentrator and dissolved in ultrapure water to achieve a concentration of approximately 0.3-0.8 µg/µl. Approximately 20 ng of the isolated IgG was pipetted into 0.2-ml skirted 96-well robotic plates (Thermo Fischer Scientific), digested with sequencing grade trypsin (Worthington), cleaned with RP SPE on Chromabond C18 ec beads (Marcherey-Nagel) and analyzed on a nanoACQUITY UPLC system (Waters) coupled to a Compact mass spectrometer (Bruker Daltonics) as described previously (Pezer et al, 2016). Tryptic glycopeptides corresponding to the Fc region of IgG were separated by LC in the gradient of 80% ACN (LC-MS purity, JT Baker, ThermoFischer Scientific) in 0.1% TFA (HPLC purity, Sigma-Aldrich) on a Halo C18 nano-LC column (150 mm × 75 µm i.d., 2.7 µm HALO fused core particles, Advanced Materials Technology), and mass spectra were recorded in positive mode.…”
Section: Analysis Of Igg Fc-linked N-glycosylation With Liquid Chromamentioning
confidence: 99%
“…I keď je glykozylácia vysoko konzer vovaným procesom, existuje niekoľko analýz, ktoré poukazujú na ich aktívne zmeny v procesoch zápalových odpo vedí u autoimunitných a infekčných ochorení [65][66][67][68] [46,47]. Efekty glykozylácií IgE pro tilátok boli preukázané mutáciami, ktoré blokovali glykozylácie v popísaných po zíciách [48].…”
Section: Regulácia Glykozylácie a Jej Fyziologické A Patologické Zmenyunclassified
“…14 The marked decrease in galactosylation and increase in agalactosylation of the three subclasses (IgG 1, 2 and 4) observed in this study have been demonstrated in many other diseases and traits, such as the Parkinson's disease and the effects of age on allergic disease. 8,26 Additionally, in many autoimmune diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus, juvenile onset chronic arthritis, and Crohn's disease, marked increase in agalactosylation has been demonstrated. [27][28][29] It can be assumed that the increase in agalactosylation and the resulting pro-inflammatory effect may be associated with many other diseases.…”
Section: By Performing Lc-esi-ms Analysis Onmentioning
confidence: 99%
“…IgG1-4), which bind their antigen targets via the fragment antigen binding (Fab) domain and exert their effector functions via the fragment crystallizable (Fc) domain. 8 Fc glycans are essential structural components of the IgG molecule and minor changes in glycan composition can significantly alter the conformation of the Fc region changing the interaction with receptor proteins and thus modulating the effector functions of IgG. The assignment of glycans to the specific Fc glycosylation sites of IgG subclasses is pivotal for deducing the functional implications of the observed glycosylation features.…”
Section: Introductionmentioning
confidence: 99%